Pagkatao, pagkababae, at seksuwalidad (Self concept, womanhood, and sexuality) a phenomenological study of the inner world of the girl child prostitute.[article]. - Fernando, Priscilla Gonzalez .
This study sought to explore the 'inner world' of female children with previous involvement in prostitution, specifically their self-concept, sense of womanhood and sexuality. Using an in-depth, multiple case-study approach, eight girls aged 14 to 17 years were interviewed using a clinical interview and projective techniques to encourage the expression of their deepest and most personal feelings, needs, issues, and attitudes. The main finding was that an emotional/conceptual 'split' had taken place, wherein the girls' self-concept, sense of womanhood and sexuality contained two widely disparate, and yet equally present, self-images: the one that had been irreparably damaged, stained, abused, and degraded by the experiences of abuse and prostitution, and therefore deserved no honor, love, or happiness; and the one that held hope for a 'new (or fantasized) me' that had dignity, was respected and loved, and had real choices and a real chance for happiness.